Effects of ambient exposure on photoluminescence of Dion–Jacobson tin-based halide perovskites. Issue 7 (6th February 2023) - Sun, Wen Ting; Xing, Zengshan; Sergeev, Aleksandr; He, Yanling; Ng, Alan Man Ching; Wong, Kam Sing; Molčanov, Lidija; Popović, Jasminka; Djurišić, Aleksandra B.
Abstract : Enhancement of light emission upon ambient exposure in tin-based Dion–Jacobson perovskites occurs due to the transformation of their non-emissive 2D phase into the emissive hydrated 1D phase. Abstract : Tin-based halide perovskite materials are of interest for light-emitting applications due to their broad yellow emission, but they are known to exhibit inferior stability compared to lead-based perovskites due to the tendency of Sn 2+ to be readily oxidized. Here, we investigated the ambient stability of a Dion–Jacobson tin bromide perovskite. We found that the optical properties of the samples were more significantly affected by moisture rather than the ratio of Sn 2+ /Sn 4+ . The exposure to humidity resulted in changes in the ratio of 2D HDASnBr4 and hydrated 1D HDA3 SnBr8 phases (where HDA denotes hexane-1, 6-diammonium), with an initial increase (up to ∼40 h) in luminescence attributed to the increasing fraction of the hydrated 1D phase which contributes to self-trapped exciton emission. With further exposure to humidity, the material starts to degrade resulting in reduced luminescence after ∼40 h. The use of additives for the suppression of oxidation of Sn 2+, namely SnCl2 and tetraethyl orthosilicate (TEOS), results in prolonging the lifetime of the samples (>260 h for thin films with additives, compared to 180 h for thin films without additives). However, the persistence of luminescence with an increased time of ambient exposure in samples prepared with additives can be attributed to the changes in the evolution of phase compositions (ratios of 2D and hydrated 1D phases) over time rather than suppression of the oxidation of Sn 2+ .